Exterior view of the walls of the mandapa - Temples of India Project Team (Jio Institute, 2024)
The mandapa of the temple is a rectangular hall with simple and plain outer walls. It has a flat roof. There are no decorative elements present on the walls except the flanking chhajja supporting the roof.